Spectral evolution of a photochemical protecting group for orthogonal two-color uncaging with visible light - Olson, Jeremy P. (2013)
Caged compounds are molecules rendered functionally inert by derivatization with a photochemical protecting group. We describe the design logic behind the development of a diethylaminocoumarin (DEAC) caging chromophore, DEAC450, that absorbs blue light strongly (ε(450) = 43,000 M(-1) cm(-1)), and violet light 10-fold more weakly. The absorption minimum is in the wavelength range (340-360 nm) that is traditionally used for photolysis of many widely used nitroaromatic caged compounds (e.g. 4-carboxymethoxy-5,7-dinitroindolinyl(CDNI)-GABA). We used this chromophore to synthesize DEAC450-caged cAMP and found this probe was very stable towards aqueous hydrolysis in the electronic ground state but was photolyzed with a quantum efficiency of 0.76. When DEAC450-cAMP and CDNI-GABA where co-applied to striatal cholinergic interneurons, the caged compounds were photolyzed in an chromatically orthogonal manner using blue and violet light so as to modulate the neuronal firing rate in a bi-directional way.